(3GNJdGa RGhjI GdQDjI HHjFI GdhGbY GdeYRR THg GdGfZeGSjI h CKQgG ai JfejI GdeaGgje GdQjGVjI h GdJNjd GdHUQi GdecGfi dOi QjGV GdCWaGd (B/ s - (3GdTjeGA eQSi eQSi CMeOs; (3eQhI eMeO LeGd GdOjf GdeMeOi (B: s; (3efGd YHOGdYGd eHGQR (B: s ((3GdbGgQI (B: s (3GdTjeGA eQSi eQSi CMeO (B: s, 2018)
(3gOa GdHMK Edi GdJYQa Ydi CKQ GNJdGa RGhjI GdQDjI HHjFI GdhGbY GdeYRR THg GdGfZeGSjI ai JfejI GdeaGgje GdQjGVjI h GdJNjd GdHUQi GdecGfi dOi QjGV GdCWaGd(B: (3h ddhUhd Edi gPG GdgOa GSJNOeJ GdHGMKI efgL GdHMK GdJLQjHi(B: (3h eQGLYI GdCOHjGJ GdJQHhjI GdSGHbI(B: (3h GdJi JJYdb HJUeje RGhjI GdQDjI HHjFI GdhGbY GdeYRR THg GdGfZeGSjI h GdeaGgje GdQjGVjI h GdJNjd GdHUQi GdecGfi(B: (3ceG Je EYOGO bGFeI HeYGjjQ JUeje RGhjI GdQDjI HHjFI GdhGbY GdeYRR THg GdGfZeGSjI(B: (3h Je GSJNOGe fehPL eMeO YWjg NejS (B(2003) (3ai JWhjQ RGhjI GdQDjI HHjFI GdhGbY GdeYRR THg GdGfZeGSjI ddMce Ydj eWGHbJgG ddeYGjjQ(B: (3ceG Je EYOGO COhGJ GdHMK hgj GNJHGQ GdeaGgje GdQjGVjI GdeUhQ(B: (3h ebjGS GdJNjd GdHUQj GdecGfi(B: (3h JchfJ YjfI GdHMK ef (B(90) (3Wad ef CWaGd eOQSI caQ TcQ GdJLQHHjI (B- (3HeMGaXI GdbdjhHjI(B: (3Je JbSjegG Edi (B3 (3eLehYGJ habkG ddJUeje GdJLQjHj ddHMK(B: (3hJe ELQGA JLQHI GdHMK hJWHjb CSGdjH GdeYGdLI GdGMUGFjI GdHGQeJQjI HGSJNOGe HQfGeL (B((3ES Hi ES ES ai(B25): (3h JhUdJ Cge fJGFL Edi Cf RGhjI GdQDjI GdeGFdI HHjFI GdhGbY GdeYRR THg GdGfZeGSjI gi GdCcKQ JCKjQkG ai JfejI GdeaGgje GdQjGVjI dOi QjGV GdCWaGd(B: (3HjfeG RGhjI GdQDjI ef CYdi gi GdCcKQ JCKjQkG ai JfejI egGQGJ GdJNjd GdHUQi GdecGfi(B: (3h JVefJ GdQSGdI edGMb GdHMK h bGFeI GdeQGLY h YOO ef GdJhUjGJ h GdCHMGK GdebJQMIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOGQSGJ GdYdjG ddJQHjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdeaGgje GdQjGVjIs; (3HjFGJ GdhGbY GdeeYRR THg GdGfZeGSjIs; (3RGhjI GdQDjIs